THE APPROACH OF ISLAMIC EDUCATION MANAGEMENT IN FACING GLOBAL CHALLENGES - Fatkhurin Fuad, Ulvia; Sholeh, Muh Ibnu; Sokip; Syafi'i, Asrop; Suwandi, Eko Agus; 'Azah, Nur; Andayani, Dwi (re-JIEM (Research Journal of Islamic Education Management), 2023)
This research aims to explore appropriate strategies for Islamic education organizations in facing global challenges. The globalization of education has brought major changes in education systems throughout the world, while technological advances, the challenges of multiculturalism, and global competition are some of the key issues faced by Islamic education organizations in facing the dynamics of educational globalization. Therefore, the management of Islamic education organizations must have the skills to face these challenges and maintain high quality in Islamic education. This research utilized a library research approach. Researchers conducted a literature review, observing writings and sources related to the research issue. Data collection was carried out by searching for sources from various media such as books, journals, and related research. Data obtained from literature observations were analyzed using an interactive qualitative approach. The data analysis process includes steps such as data collection, data reduction, data presentation, and conclusion. The conclusion that can be drawn from this research is that an effective approach to facing global challenges involves improving quality, innovation, cooperation, understanding the challenges of multiculturalism, and increasing human resource capacity. These steps are expected to help the management of Islamic education organizations maintain the quality and relevance of education in the face of changes in the globalization of education.